The Spiritual Life of Medical Missionary William Lockhart - YU Qiang, (Journal of Research for Christianity in China (JRCC), 2017)
William Lockhart was the first medical missionary sent to China by the London Missionary Society of Britain. He came to China twice and served there for nearly twenty-five years. He founded Shanghai Renji Hospital and Peking Union Medical College Hospital, making an indelible contribution to the spread of Western medicine in China. Currently, research on William Lockhart remains limited, primarily scattered across studies of modern Chinese medical history and missionary work in China, with a focus on his achievements in medical missionary endeavors. This paper does not intend to reiterate or emphasize this aspect. Instead, based on a newly acquired collection of materials—correspondence from the Lockhart family—it seeks to explore his spiritual life during his service in China from the perspective of a Christian missionary. This approach may offer a fresh perspective on Western missionaries who came to China in the modern era.